Antifungal effectiveness of soursop (Annonamuricata Linn) leaves extract againts Candida albicans on heat cured acrylic: Efektivitas antifungi ekstrak daun sirsak (Annonamuricata Linn) terhadap Candida albicans pada akrilik polimerisasi panas - Ria Koesoemawati (Makassar Dental Journal PDGI Makassar, 2021)
Objective: The use of removable dentures can cause chronic inflammation, namely denture stomatitis, caused by Candida al-bicans; with a prevalence of 15-70%. Soursop (Annonamuricata Linn) leaf extract contains alkaloids, tanin, flavonoids, and sa-ponins that act as antifungals. This study is intended to evaluate whether soursop leaf extract solution can effectively reduce the number of C.albicans colonies in heat polymerized acrylic resins. Method: With true experimental pre-post test with control group design, 25 resin plates were divided into 5 groups, 3 groups were tested with soursop leaf extract (10%, 15% and 25%), while Fittydent® and aquadest were the control groups. Samples are contaminated with C.albicans suspension and incubated; calculated before immersion 8 hours, then put in Saboroud's brouth and recalculated. Result: Wilcoxon test showed significant differences in all groups, except the aquadest group. The Mann-Whitney test compared a decrease in the number of C.albicans colonies between groups, showed significant differences between treatment groups, except between the extract group of 25% and fittydent control®. Conclusion: Soursop leaf extract solution lowers the number of C.albicans colonies in heat polymeri-zation acrylic with the most effective concentration of 25%.